Antiviral Activity of Ivermectin Against SARS-CoV-2: An Old-Fashioned Dog with a New Trick-A Literature Review - Mudatsir Mudatsir; Amanda Yufika; Firzan Nainu; Andri Frediansyah; Dewi Megawati; Agung Pranata; Wilda Mahdani; Ichsan Ichsan; Kuldeep Dhama; Harapan Harapan (MDPI AG, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is a major global threat. With no effective antiviral drugs, the repurposing of many currently available drugs has been considered. One such drug is ivermectin, an FDA-approved antiparasitic agent that has been shown to exhibit antiviral activity against a broad range of viruses. Recent studies have suggested that ivermectin inhibits the replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), thus suggesting its potential for use against COVID-19. This review has summarized the evidence derived from docking and modeling analysis, in vitro and in vivo studies, and results from new investigational drug protocols, as well as clinical trials, if available, which will be effective in supporting the prospective use of ivermectin as an alternative treatment for COVID-19.